National Consultation Workshop on Digital Innovation and Inclusion - Malhotra, Aayushi; Gakhar, Shalini; Sharma, Sheetal; Dominic, Ditty Maria; Sulaiman, V. Rasheed (International Rice Research Institute, 2023)
The National Stakeholder Consultation workshop, held in New Delhi on December 4, 2023, marked a pivotal step in advancing digital innovation and inclusion in agriculture. Jointly organized by the CGIAR Digital Innovation (DI) Initiative team from IRRI and IWMI, along with CRISP, this workshop served as a platform for sharing progress on the Digital Inclusion Index (DII) and the implementation of the Rice Crop Manager (RCM) within India's dynamic agri-digital ecosystem. The DII, still in its early stages, is designed to address multifaceted challenges in food systems, while the RCM integrates digital technology with scientific research to provide tailored nutrient and crop management advice, aiming to enhance yields and farmer incomes. The workshop's objectives centered around raising awareness and refining the DII, fostering collaboration for its pilot implementation, documenting best practices for digital inclusion, and supporting digital innovators in leveraging underutilized data assets to improve digital innovation quality and efficiency. Engaging 38 participants from diverse sectors including NGOs, research, and digital solution management, the workshop catalyzed a collaborative effort to propel digital inclusion and innovation in agriculture forward.